Water productivity monitoring: Ethiopia - Tadesse, Mulugeta; Muleta, D.; Schmitter, Petra; Dembélé, Moctar (International Water Management Institute, 2025)
The Wheat Water Productivity Tool (WWPT) uses WaPOR data to enhance land and water productivity in both rainfed and irrigated wheat cultivation, integrating biophysical and socioeconomic factors to improve the eﬀectiveness of agricultural extension advisory services.